2007
DOI: 10.1002/art.22328
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal induction of transforming growth factor β signaling in fibroblasts of mice recapitulates clinical, histologic, and biochemical features of scleroderma

Abstract: Objective. Increased signaling by transforming growth factor ␤ (TGF␤) has been implicated in systemic sclerosis (SSc; scleroderma), a complex disorder of connective tissues characterized by excessive accumulation of collagen and other extracellular matrix components in systemic organs. To directly assess the effect of sustained TGF␤ signaling in SSc, we established a novel mouse model in which the TGF␤ signaling pathway is activated in fibroblasts postnatally.Methods. The mice we used (termed TBR1 CA ; Cre-ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 38 publications
5
127
0
7
Order By: Relevance
“…However, we detected no differences in the level of either plasminogen or PAI-1 between the groups, suggesting that neither plasminogen nor PAI-1 could account for reduced plasmin activity. It should be noted that some studies have shown elevated PAI-1 levels in fibroblasts from patients with SSc (42)(43)(44)(45), while other studies have not (46)(47)(48). It is not clear why results differ in this regard, other than due to relatively small sample sizes in all studies and the high heterogeneity of the SSc patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, we detected no differences in the level of either plasminogen or PAI-1 between the groups, suggesting that neither plasminogen nor PAI-1 could account for reduced plasmin activity. It should be noted that some studies have shown elevated PAI-1 levels in fibroblasts from patients with SSc (42)(43)(44)(45), while other studies have not (46)(47)(48). It is not clear why results differ in this regard, other than due to relatively small sample sizes in all studies and the high heterogeneity of the SSc patient population.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b also inhibits ECM degradation by downregulating MMP-1, which mediates collagen degradation, and up-regulating tissue inhibitors of matrix metalloproteinases (TIMPs) (Ihn 2005). Activation of the TGF-b pathway in postnatal fibroblasts is sufficient to induce skin fibrosis in mice, including epidermal thinning, loss of hair follicles and dermal fibrosis (Sonnylal et al 2007). Dermal accumulation of collagen type I and III and up-regulation of other ECM proteins, including fibronectin, osteopontin, and SPARC, are observed.…”
Section: Fibrosismentioning
confidence: 99%
“…Our group recently developed 2 complementary transgenic mouse strains with fibroblast-specific activation of TGF␤ signaling that demonstrate hallmark pathologic features of SSc. One strain has inducible ligand-independent activation of TGF␤ signaling and develops skin and vascular fibrosis (11). The other transgenic strain (T␤RII⌬k-fib) demonstrates balanced ligand-dependent activation of TGF␤ signaling (12)(13)(14) and is examined further in this study.…”
mentioning
confidence: 99%